1991
DOI: 10.1212/wnl.41.11.1785
|View full text |Cite
|
Sign up to set email alerts
|

Felbamate for partial seizures

Abstract: Felbamate (2-phenyl-1,3-propanediol dicarbamate) has a favorable preclinical profile in animal models of epilepsy. We present the results of a double-blind, randomized, placebo-controlled clinical trial in patients with partial seizures. Criteria for entry included a requirement for four or more partial seizures per month despite concomitant therapeutic blood levels of phenytoin and carbamazepine. Fifty-six patients (mean age, 31.4 years; 32 men, 24 women) completed the trial. The mean seizure frequencies for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(63 citation statements)
references
References 0 publications
2
60
1
Order By: Relevance
“…2,3 In both the adult and pediatric population, concomitant AEDs should be reduced by a minimum of 20% when starting felbamate, and may be reduced further if levels are high. 1 Felbamate is generally well tolerated, with the most common adverse effects being insomnia, dizziness, fatigue, decreased appetite, weight loss, nausea, ataxia, and lethargy.…”
Section: Felbamatementioning
confidence: 99%
See 1 more Smart Citation
“…2,3 In both the adult and pediatric population, concomitant AEDs should be reduced by a minimum of 20% when starting felbamate, and may be reduced further if levels are high. 1 Felbamate is generally well tolerated, with the most common adverse effects being insomnia, dizziness, fatigue, decreased appetite, weight loss, nausea, ataxia, and lethargy.…”
Section: Felbamatementioning
confidence: 99%
“…1 Felbamate is generally well tolerated, with the most common adverse effects being insomnia, dizziness, fatigue, decreased appetite, weight loss, nausea, ataxia, and lethargy. [2][3][4][5] In 110,000 patients, there were 10 cases of fatal aplastic anemia and 14 cases of fatal hepatic failure. The labeling was changed to advise that it be utilized in a limited subset of patients along with bi-weekly blood monitoring.…”
Section: Felbamatementioning
confidence: 99%
“…Though its exact mechanism of action is undefined, predinical evaluations have indicated that felbamate appears to increase seizure threshold and prevent seizure spread (65). In controlled clinical studies, felbamate has demonstrated efficacy as adjunctive therapy in the treatment of partial and generalired seizures in adults (66)(67)(68). In addition, felbamate as monotherapy was superior to a nontherapeutic dose of valproic acid (69,70).…”
Section: New Antiepileptic Medicationsmentioning
confidence: 99%
“…The efficacy of FBM was shown in trials in which FBM was added to phenytoin (PHT) and carbamazepine (CBZ) in patients with partial epilepsy ( 17), patients with partial seizures who were undergoing presurgical evaluation ( 18), and as monotherapy in uncontrolled partial epilepsy (19). The approval in children was primarily based on a multicenter study of 73 patients with LennoxGastaut syndrome that compared the efficacy of FBM to that of placebo as adjunctive therapy to concurrent AEDs (20).…”
mentioning
confidence: 99%